Effect of Spiritual Intelligence Training on Psychological Hardiness and Social Vitality in Students Post-COVID-19 - Hadi Pordel (Health, Spirituality and Medical Ethics)
Background and Objectives: Given the widespread impacts of the COVID-19 pandemic on various aspects of life, including education, the need for effective strategies to enhance students’ psychological hardiness and social vitality is felt more than ever. Spiritual intelligence, as a psychological aspect, can play a significant role in improving these two components. This research aimed to investigate the effectiveness of spiritual intelligence training in enhancing students’ psychological hardiness and social vitality in the post-COVID-19 period. Methods: This quasi-experimental employed a pre-test-post-test design with a control group. The statistical population included male secondary school students in Qom City, Iran. Thirty students from a school in District 1 of Qom City were selected using the convenience sampling method and randomly assigned to two groups of 15. The experimental group participated in ten sessions of spiritual intelligence training, while the control group received no training. Both groups were assessed using the psychological hardiness scale by Long and Golat (2003) and the social vitality scale by Zare and Aminpour (2011) before and after the intervention and at the follow-up stage. Data were analyzed using SPSS software, version 22 and repeated measures analysis of variance (ANOVA). Results: Spiritual intelligence training significantly influenced the psychological hardiness and social vitality of students in the post-COVID-19 period (P<0.01). Conclusion: The study’s results emphasize the importance of using educational programs based on spiritual intelligence to enhance students’ psychological and academic capabilities. This can be an effective strategy in educational and training planning.